Transformation of Moderation in The Independent Curriculum In Educational Institutions in The Pesantren Environment - Syamsul Arifin (Postgraduate Program, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2023)
Religious moderation is a moderate understanding and practice of worship in religion, balanced not extreme and excessive. This article will explore the transformation in the application of religious moderation whose character values are contained in the pancasial learner profile developed in the independent curriculum in modern and semi-modern cottage educational institutions. In this article applying qualitative studies, the analysis used in this study is in accordance with the principles of qualitative research, namely data collection, data processing and analysis carried out simultaneously during the research process. In this study, it is concluded that in the Pancasila Student Profile developed by the independent curriculum, there is a value of Religious Moderation, Pancasila Students as the Realization of Indonesian Students Who Have Global Competence and Behave in Accordance with the Values of Pancasila, Which has the Value of Believing, fearing God Almighty, and having Noble Morals, Diversity, Gotong royong Mandiri Critical and Creative Reasoning. While religious moderation as a perspective related to the process of understanding and practicing religious teachings so that in the profile of Pancasila students so that it is always in the nuances of Tawassut, Tawazun, I'tidal, Tasamuh, Musawah, Shura, al-Ishlah, Tatawwurwal Ibtikar, Tahaddur, Wataniyah wa Muwatanah and al-Qudwah.Islamic moderation is very important to be applied in efforts to create a tolerant, peaceful, and safe social order. Islamic moderation is the realization or manifestation of Islam rahmatan lil 'alamin. Moderate principles should be embedded and realized in the behavior and attitudes of Muslims, both individuals and groups, in various aspects of life, especially in the world of education.